ASSESSMENT OF WATER POLLUTION IN MALAKA-HARHAR WETLAND OF ALLAHABAD - ANAND MOHAN, (International Journal of Pharma and Bio Sciences, 2014)
The assessment in pollution parameters of Malaka-Harhar wetland in Allahabad, like Temperature, pH, D.O., B.O.D. and electrical conductivity was analyzed from (Sep. 2008-Aug. 2009). All these parameters were found to be higher in cool season compare to other season may be due to the temperature change which shows a inverse relationship with water temperature. The water was alkaline during entire study period and alkalinity was found highest in the month of June and lowest in the month of August. This study reveals the changes in physico-chemical characteristics of this wet land, which will be a beneficial study to monitor the environmental changes of such water bodies.